The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2495/tdi-v1-n2-129-136
|View full text |Cite
|
Sign up to set email alerts
|

From horizontal collaboration to the physical internet – A case study from austria

Abstract: The growing global flow of goods, the increasing problem of traffic congestion and the inefficiencies associated with distribution and logistics or the discerning consumers' high standards for products and delivery services lead to new logistical requirements, for which the model of the 'Physical Internet' has emerged as a probable solution. Physical Internet is a novel concept that transforms how physical objects are designed, manufactured and distributed aiming for a radical sustainability improvement. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…Combine Vertical and Horizontal Collaboration. Finally, case studies such as Simmer et al (2017) or Mason et al (2007) call for more closely integrated vertical and horizontal collaboration to fully achieve concepts of the Physical Internet. To achieve this, operational planning models need to be extended beyond the categories this literature survey followed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Combine Vertical and Horizontal Collaboration. Finally, case studies such as Simmer et al (2017) or Mason et al (2007) call for more closely integrated vertical and horizontal collaboration to fully achieve concepts of the Physical Internet. To achieve this, operational planning models need to be extended beyond the categories this literature survey followed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Theoretically, this scenario could apply to the centralized control of all flows in a conventional logistics network (i.e., traditional resource pooling without implementing PI). However, Simmer et al (2017), for example, note that actors are unwilling to relinquish control. Thus, centralized control in a conventional logistics system is deemed unrealistic (unless the environment creates urgency toward it as in Hagebäck and Segerstedt (2004)).…”
Section: The Modelmentioning
confidence: 99%
“…No research was found on how PI could gradually be adopted to replace current logistics operations, but Simmer et al (2017) interviewed logistics service providers in Austria in order to identify adoption challenges:The majority of companies consider the external digitization, meaning the interfaces with customers, as the greatest challenge, but also data processing and standard data exchange were frequently mentioned. Further challenges, which were rarely suggested, pertain to the retention of flexibility, the capital expenditure, the scope of interconnection without interface rupture, the changes in professional profiles and the need to always have state-of-the-art technology (p. 131).…”
Section: The Pi – Reviewmentioning
confidence: 99%